The Effect of Problem-Based Learning E-Module on Students’ Problem-Solving Skills in Heat and Heat Transfer Topics at SMAN 2 Koto XI Tarusan - Afifah, Azzah (Physics Learning and Education, 2025)
This research intends to examine how Problem-Based Learning (PBL)-based e-modules influence students' problem-solving skills regarding heat and heat transfer concepts. The study was driven by the inadequate problem-solving abilities noted in students at SMAN 2 Koto XI Tarusan, mainly because of the prevalence of expository teaching techniques and the constraints of traditional learning resources. A quantitative method utilizing a quasi-experimental non-equivalent control group design was utilized. The sample comprised 60 Grade XI students split into two groups: one group utilized PBL-based e-modules, whereas the other group employed traditional materials. Data were gathered through pretests and posttests consisting of essay questions. The Mann-Whitney U test was utilized because the data did not follow a normal distribution. Findings showed a notable difference in problem-solving skills between the two groups. The experimental group demonstrated a significant rise in the average score of the posttest (77.10) in contrast to the pretest (40.03), whereas the control group saw a slight increase from 44.00 to 58.07. Enhancements were noted in all problem-solving metrics. Analysis of data using the Mann-Whitney test indicated a statistically significant difference in problem-solving abilities between the experimental group and the control group. The findings from the Mann-Whitney test showed a significance level of <0.05, thereby underscoring a significant impact of the use of project-based learning (PBL) e-modules on improving students' problem-solving skills specifically concerning heat and thermal transfer. This methodological framework has demonstrated success in tackling current challenges, aligning with the requirements of 21st-century skills and the implementation of the Independent Curriculum.